Synthesis and Characterization of Organometallic Chalcones Functionalized with a Crown Ether Fragment. Spectroscopic and Electrochemical Behavior - Pavez-Irrazabal, J; Pavez-Irrazabal, J; Godoy-Gonzalez, F; Godoy-Gonzalez, F; Silva-Molina, C; Silva-Molina, C; Gomez-San Martin, A; Gomez-San Martin, A; Agurto-Doren, N; Agurto-Doren, N; Maldonado-Hernandez, T; Maldonado-Hernandez, T (Elsevier B.V., 2017)
Organometallic chalcone complexes functionalized with a macrocyclic fragment [(η5-C5H4C(O)CH[dbnd]CH-4-benzo-15-crown-5)MLn] (ferrocenyl, cyrhetrenyl, and cymantrenyl) have been synthesized. The complexes are characterized by IR spectroscopy,1H and13C NMR spectroscopies, elemental analyses, and HR-MS. The stereochemistry for the chalcone compounds was determined using the1H and13C NMR spectroscopy data, which indicated that they are isolated as a single isomer (E). In addition, the syntheses of the chalcone-imine derivatives are described, and they adopt an anti-(E,E) conformation in solution, confirmed by the X-ray crystal structures in the solid state. The UV–Visible and electrochemical behavior of the organometallic complexes are reported. © 2016 Elsevier B.V.